2022
DOI: 10.3390/molecules27113640
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility Assessment of Polylactic Acid (PLA) and Nanobioglass (n-BG) Nanocomposites for Biomedical Applications

Abstract: Scaffolds based on biopolymers and nanomaterials with appropriate mechanical properties and high biocompatibility are desirable in tissue engineering. Therefore, polylactic acid (PLA) nanocomposites were prepared with ceramic nanobioglass (PLA/n-BGs) at 5 and 10 wt.%. Bioglass nanoparticles (n-BGs) were prepared using a sol–gel methodology with a size of ca. 24.87 ± 6.26 nm. In addition, they showed the ability to inhibit bacteria such as Escherichia coli (ATCC 11775), Vibrio parahaemolyticus (ATCC 17802), Sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 66 publications
(87 reference statements)
0
1
0
Order By: Relevance
“…Polylactide (PLA) was chosen as a control because it has been shown to be biocompatible in previous studies. [ 78,79 ] The results (see Figure ) showed that the NFC/Alg samples were compatible with the tested cells (HEK‐293).…”
Section: Resultsmentioning
confidence: 74%
“…Polylactide (PLA) was chosen as a control because it has been shown to be biocompatible in previous studies. [ 78,79 ] The results (see Figure ) showed that the NFC/Alg samples were compatible with the tested cells (HEK‐293).…”
Section: Resultsmentioning
confidence: 74%
“…42 PLA/n-BG nanocomposites were also found to be safe for healing processes such as bone tissue repair and avoiding microbial contamination. 43 If PLA properties are enhanced with modifications that can be made when mixed with other polymers, the treatment spectrum of diseases with PLA will be enlarged. 44 Indeed, Moghaddam et al claimed that PLA is toxic-free and can be used instead of wet gauze as a breast bolus for surface dose enhancement and dose uniformity improvement during breast intraoperative electron radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…The synthesis and characterization of n-BG with a ternary system (54%-SiO 2 :40%-CaO:6%-P 2 O 5 ) have been reported elsewhere [21].…”
Section: Synthesis Of N-bgmentioning
confidence: 99%
“…The main disadvantage is the adequate control of porosity, which requires specific conditions; therefore, these conditions can affect the nucleation phenomena that are ideal for biomedical procedures [18][19][20]. Our group previously published a work demonstrating the advantage of incorporating n-BG type 45S5 in polylactic acid (PLA) scaffolds to improve their biocompatibility and reinforce their thermal and mechanical resistance [21].…”
Section: Introductionmentioning
confidence: 99%